SPEED CONTROL OF BLDC MOTOR USING PV AND SEPIC CONVERTER - Reenamol Robert; Sandhya P. (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper is based on Speed control of BLDC motor using PV and SEPIC converter. Nowadays BLDC motor drive is more used as it has many advantages like high power density, high efficiency etc. Solar Panels have become an increasingly popular form of renewable energy. Photovoltaics (PVs) is the input source to SEPIC converter. SEPIC converter have high voltage ratings which can operate in step up and step down mode. For commutation by electronic switches three phase voltage source inverter is used. BLDC motor winding of stator is connected to Electronic commutator. A closed loop operation of BLDC motor to attain speed control is used by PI controller. The components are simulated in MATLAB 2019b software. And the simulation results are presented.